BIOECONOMIC EVALUATION OF A SORGHUM CONSORTIUM WITH DIFFERENT FORAGE SPECIES FOR AN INTEGRATED CROP-LIVESTOCK SYSTEM IN NOVA PORTEIRINHA, MG - Ferrazza, Rodrigo de Andrade [UNESP]; Lopes, Marcos Aurelio; Brant Albuquerque, Carlos Juliano (Inst Zootecnia, 2016)
The objective of this study was to evaluate the bioeconomic feasibility of a consortium of sorghum and different forage species for an integrated crop-livestock production system (ICLS) in the municipality of Nova Porteirinha, MG. In the first year of the experiment, seven grass species were sewn together with sorghum for pasture formation, in addition to sorghum alone, at two spacings (40 and 80 cm), defining 16 treatments: a) Brachiaria decumbens + sorghum; b) B. brizantha + sorghum; c) B. ruziziensis + sorghum; d) Cenchrus ciliaris cv. Aridus + sorghum; e) C. ciliaris cv. 131 + sorghum; f) Panicum maximum + sorghum; g) Andropogon gayanus + sorghum; h) sorghum alone. In the second agricultural year, the forages were previously removed for direct seeding of sorghum. The economic efficiency indicators used were simple payback, discounted payback, net present value, internal rate of return, and benefit-cost ratio. Significant differences (P<0.01) were observed for the effect of consortium, spacing and the interaction consortium x spacing on sorghum productivity. There were significant differences for the effect of consortium (P<0.01), spacing (P<0.01) and interaction consortium x spacing (P<0.05) on dry matter productivity of the forage. Six of the 14 treatments analyzed for the ICLS exhibited greater economic feasibility and attractiveness when compared to sorghum alone. The most recommended consortium was sorghum grown with B. ruziziensis and B. brizantha at spacings of 80 and 40 cm, respectively, due to its high productivity and low cost of pasture implantation.
Keywords: beef cattle farming; crops; semiarid; Sorghum bicolor L.; decision-making